Tahapan Pembuatan Peraturan Daerah Terkait Pendidikan Di Kabupaten Solok - Yosi Angel Dirawati (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This study examines the process of formulating regional education regulations in Solok Regency, focusing on the stages from planning to implementation. The research employs a qualitative approach through observation and in-depth interviews with stakeholders involved in the formulation of education policies. The findings reveal that the regional regulation process begins with the Regional Regulation Formation Program (Propemperda), followed by problem identification, policy agenda setting, policy formulation, discussion in the Regional House of Representatives (DPRD), ratification, and implementation. Various challenges were identified in the implementation phase, including budget constraints, limited land availability, restrictive national regulations, and cultural resistance to certain policies. The study recommends strengthening community involvement in the regulatory process, adequate budget allocation, harmonization between regional and national policies, cultural approaches to implementation, comprehensive monitoring and evaluation systems, and improving educational facility accessibility for all community members, including those with disabilities and the elderly.